The Use of Time by Academic Teachers (Poznań University of Economics and Business Example) - Olejniczak, Magdalena; Andrzejczak, Aldona (Studia Oeconomica Posnaniensia, 2017)
The aim of this article is to analyze the distribution time of academics especially in the context of the time division between professional and non-professional tasks as well as the balance between academic work, teaching and administration. The article introduces the problems of time management. The empirical part contains a presentation of the results of research conducted among academics of the Poznań University of Economics and Business in November 2013. The analyses show that academics have a high focus on professional activity. The proportion of the use of time indicates a priority to perform tasks related to teaching and scientific work, with the significant participation of organizational duties. In practice, it often comes to the reallocation of time for science activity to fulfill teaching duties, accompanied by a feeling of underestimation, especially in their teaching.